Food parenting stress among caregivers receiving government food assistance: a study from the United States - Faith Hardy; Alison Tovar; Emily G. Elenio; Yarisbel Melo Herrera; Michelle Perry; Katherine W. Bauer; Maya K. Vadiveloo (Preventive Medicine Reports)
Objective: Caregivers are expected to implement child feeding recommendations such as providing healthy meals and promoting family meals. However, these expectations may contribute to stress, particularly for families without food security. This study examined food parenting stress and its variation by household food security. Methods: Baseline data, from Rhode Island and Connecticut (May–September 2023) from an ongoing study assessing the impact of a state-wide incentive program for Supplemental Nutrition Assistance Program participants, were used. Primary caregivers completed an online survey, with socio-demographic questions, household food security, and a Likert-type-scale assessing feeding stressors. Associations between stressors and food security were analyzed using chi-square-tests and multivariable logistic regression. Results: Among 779 respondents, nearly half of respondents reported that making sure their child eats the right amount of food (46 %), the right kind of food (49 %), and healthy food outside the home (50 %) was ‘moderately’, ‘very’, or ‘extremely’ stressful. Households that did not experience food security had significantly higher odds of reporting stress across all feeding situations vs. those with food security, adjusting for covariates. Conclusions: Food parenting stress is common and heightened among those that are not food secure. Nutrition education should be paired with supports that address structural barriers.